Time pick-off method by using the automatic gain control (AGC) - Hansang Lim; Jooyoung Yoon; Sanghyun Min; Jaehong Park (2001 IEEE Nuclear Science Symposium Conference Record (Cat. No.01CH37310), 2001)
Time pickoff method by using the automatic gain control (AGC) is presented to reduce the timing walk for a multi-gap resistive plate chamber (MRPC). Due to both variations in the size of the signal and the slew rate of the signal, triggering by threshold level for time measurement is subject to problems of time walk. In addition, comparator response time is a function of the signal slew rate and this is the dominant timing error in the CFD and the zero-crossing discriminator. We add the AGC circuit between the preamplifier and the discriminator in the front-end module (FEM) so that the signals have the same size and the same slew rate. We show the feasibility of this time pick-off method with AGC using the SPICE circuit analysis program.